Financial Sustainability: The Effect Of Fraud Triangle On Financial Statement Fraud - Rahmawati, Alni; Dita Pramesty, Andriana (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to determine the influence of Fraud Triangle Theory on financial statement fraud. This research uses a sample of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange using the Purposive Sampling method. This research is quantitative research using primary data based on financial reports published by the Indonesian Stock Exchange. The sample in this study was 174. Hypothesis testing in this study used multiple regression analysis and MRA (Moderated Regression Analysis) through the EViews 12 application. Based on the results of the analysis carried out, it was found that (1) Financial stability had a positive effect on fraud, (2) Ineffective monitoring did not influence on fraud. (3) Change in Auditor has a positive effect on fraud, (4) Audit committee is a non-moderating variable of financial stability on financial statement fraud. This research can provide insight as well as knowledge about how one financial reporting fraud can be measured using the Beneish M Score formula. The results can be used by the company so that the company can present financial statements free of fraud that are material so that they do not develop into a scandal because they have a strong influence on the economic decision-making of investors, creditors, and other stakeholders. The study focuses only on manufacturing companies listed on the Indonesian stock exchange for the period 2018-2022 and uses the Beneish M-score formula as a measure to detect fraudulent financial reporting